2014
DOI: 10.4236/fns.2014.511113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxygenic Activity of <i>Solanum nigrum L.</i> Leaves in Sunflower Oil Model System and Its Thermal Stability

Abstract: The antioxygenic activity of Solanum nigrum L. leaves and its various solvent extracts were evaluated using sunflower oil model system. Leaf powder and its methanol/water (80:20) soluble fraction showed strong antioxygenic activity in refined sunflower oil. On the other hand, ethyl acetate fraction exhibited marginal antioxygenic activity, whereas the water soluble fraction was practically devoid of any activity in refined sunflower oil. Thermal stability of different extracts of Solanum nigrum L. leaves heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
3
5
2
3
Order By: Relevance
“…The result also similar to its water leaves extract which expressed the highest TFC (5.20 mg CE/g extract) compared to calyx, peel, pulp and stem extracts [22]. Padmashree et al [30] reported that methanol-water (4:1) leaves extract of S. nigrum had the highest TFC (1.51 g/100 g) compared to methanol extract (1.01 g/100 g), ethyl acetate extract (0.65 g/100 g), and water extract (0.54 g/100 g). Study by Kandoliya et al [15] figured that methanolic pulp extract of sample GBL-1 showed the highest TFC (13.25 mg QE/100 g) among six varieties of eggplant.…”
Section: Discussionsupporting
confidence: 61%
“…The result also similar to its water leaves extract which expressed the highest TFC (5.20 mg CE/g extract) compared to calyx, peel, pulp and stem extracts [22]. Padmashree et al [30] reported that methanol-water (4:1) leaves extract of S. nigrum had the highest TFC (1.51 g/100 g) compared to methanol extract (1.01 g/100 g), ethyl acetate extract (0.65 g/100 g), and water extract (0.54 g/100 g). Study by Kandoliya et al [15] figured that methanolic pulp extract of sample GBL-1 showed the highest TFC (13.25 mg QE/100 g) among six varieties of eggplant.…”
Section: Discussionsupporting
confidence: 61%
“…High nutritional composition of S. nigrum has also been widely reported (Edmonds and Chweya 1997;Odhav et al 2007;Akubugwo et al 2007;Padmashree et al 2014;Nupo et al 2013). …”
Section: Introductionmentioning
confidence: 87%
“…También se calcularon los valores de Q10 para la degradación térmica de la actividad antioxidante del extracto de B. orellana L. a las condiciones de almacenamiento. En la tabla 3 se aprecia que el valor de este parámetro al igual que los anteriores parámetros térmicos tiene la misma tendencia y valores similares que para los compuestos fenólicos, lo cual ratifica que las propiedades antioxidantes de los extractos de B. orellana L. se deben a los compuestos fenólicos (Padmashree et al, 2014).…”
Section: Estabilidad De Los Compuestos Fenólicos Y La Actividad Antiounclassified
“…2018). Sin embargo dichos compuestos, pueden ser vulnerables a la luz, temperatura (Kırca et al, 2007;Albarici y Pessoa, 2012), contenido de sólidos (Kırca et al, 2007), pH (Reyes y Cisneros-Zevallos, 2007;He et al, 2015), oxígeno (Kırca et al, 2007;Garzón, 2008), ácido ascórbico (Garzón, 2008) y tipo de solvente en que se tengan los extractos, en cuyo caso, en el agua se tiene una de las menores estabilidades térmica (Padmashree et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation